Resistance status and physiological activity test of Spenochlea zeylanica and Ludwigia octovalvis in paddy field to 2,4-D and metsulfuron-methyl herbicides - RIZKY RAHMADI; NANIK SRIYANI; YUSNITA YUSNITA; HIDAYAT PUJISISWANTO; DWI HAPSORO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahmadi R, Sriyani N, Yusnita, Pujisiswanto H, Hapsoro D. 2021. Resistance status and physiological activity test of Spenochlea zeylanica and Ludwigia octovalvis in paddy field to 2,4-D and metsulfuron-methyl herbicides. Biodiversitas 22: 2829-2838. Spenochlea zeylanica and Ludwigia octovalvis are dominant in Trimurjo paddy fields in Central Lampung Regency, Lampung, Indonesia and difficult to control with 2,4-Dichlorophenoxyacetic acid (2,4-D) and metsulfuron-methyl herbicides that had been used for more than 12 years. This study aims to determine the resistance status of S. zeylanica and L. octovalvis and physiological activity in resistance and susceptible of both weeds species exposed to  2,4-D and metsulfuron-methyl herbicides. The study was conducted from August to December 2019 in the Greenhouse Botanical Garden of Sumatra Institute of Technology. The study used a split-plot design, the origin of weed species as the main plot and herbicide dose as the subplot. S. zeylanica exposed has low-level resistance to 2,4-D and metsulfuron-methyl herbicides with resistance Index (RI) of 2.19 and 2.87, respectively. L. octovalvis exposed was still classified as susceptible to 2,4-D and metsulfuron-methyl herbicides with RI of 1.00 and 1.59, respectively. The physiological activities (carbon assimilation, stomatal conductance, and transpiration rate) of S. zeylanica resistant to 2,4-D and metsulfuron-methyl herbicides is higher than S. zeylanica susceptible 2,4-D and metsulfuron-methyl herbicides